2007
DOI: 10.1590/s1516-84842007000300003
|View full text |Cite
|
Sign up to set email alerts
|

Fisiopatologia das doenças falciformes: da mutação genética à insuficiência de múltiplos órgãos

Abstract: endothelial cells, leukocytes and platelets, and their role in the pathophysiology of vaso-occlusion. The clinical manifestations, like anemia, pain crises and multiorgan dysfunction are covered. Factors that modulate disease severity, like the co-inheritance of αthalassemia, gene mutations related to thrombophilia and the elevation of fetal hemoglobin are discussed. Rev. bras. hematol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
50

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(103 citation statements)
references
References 20 publications
(18 reference statements)
1
49
0
50
Order By: Relevance
“…It is particularly useful in protecting against the sickling process and decreasing the hemolysis degree (4,13,24) . Although not significant, in our study MetHb levels showed a decreasing trend in patients with SCA who had higher HbF concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is particularly useful in protecting against the sickling process and decreasing the hemolysis degree (4,13,24) . Although not significant, in our study MetHb levels showed a decreasing trend in patients with SCA who had higher HbF concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…With this change, the hemoglobin molecule spatial structure is modified, forming aggregates of filaments that polymerize and precipitate, leaving the cell with sickle appearance. This phenomenon is largely responsible for the clinical features presented of patients with SCA (24) .…”
Section: Introductionmentioning
confidence: 99%
“…Anemia falciforme (AF) foi a primeira doença de base molecular que demonstrou que a hemoglobina destes pacientes tinha excesso de carga positiva em comparação com hemoglobinas de adultos saudáveis (Galkin et al, 2007;Zago & Pinto, 2007).…”
Section: Processo De Falcização Das Hemáciasunclassified
“…Consideramos que os fatores socioeconômicos também contribuem significativamente para a variabilidade clínica e de prognóstico de pessoas com doença falciforme. As condições de moradia, a qualidade e quantidade insuficiente da alimentação ingerida e a carência de assistência à saúde, muitas vezes, estão associadas à discriminação racial, baixa renda e baixa escolaridade (Zago;Pinto, 2007).…”
Section: Introductionunclassified